Research Progress in Epoxidation of Light Small-Molecule Olefins - Guanghui Zhao; Tianfu Yang; Jincheng Liu; Xianming Xu; Yulong Wang; Yongjun Zhang; Meng Gao; Chao Xiong; Hongbing Ji (Molecules)
Light olefins, as important bulk raw materials in the petrochemical industry, play an irreplaceable role in the development of the manufacturing industry and the economy. The epoxides of light olefins are important intermediates for the synthesis of polymers, drugs, and fine chemicals, and their green, efficient, and safe synthesis has attracted much attention. This review focuses on the research progress of light olefin epoxidation and elucidates traditional epoxidation methods, such as the chlorohydrin method. Although these processes have mature processes, they have drawbacks, including equipment corrosion, environmental pollution, poor safety, and high waste emissions. Special emphasis is placed on catalytic epoxidation systems using oxygen or organic peroxides as oxygen sources. For homogeneous catalytic systems, certain metal complexes exhibit high activity and selectivity yet are difficult to separate and recycle. Moreover, heterogeneous catalytic systems have become a research hotspot due to their advantages of easy separation and reusability, with supported metal catalysts being a prime example. Meanwhile, the effects of reaction temperature, pressure, solvent, etc., on epoxidation are explored. The specific reaction mechanisms are also studied and analyzed. Current research challenges, including enhancing catalyst stability and reducing costs, are summarized. In the future, developing highly efficient, green, and economically viable epoxidation technologies for large-scale industrial applications represents an important research direction in this field.